Solitary Fibrous Tumor of the Uterus - Po-Wei Chu; Jah-Yao Liu; Yi-Jen Peng; Mu-Hsien Yu (Elsevier, 2006)
Objective: A solitary fibrous tumor is an uncommon soft-tissue tumor and rarely occurs in the uterus. We present such a case. Case Report: A 78-year-old woman presented with low abdominal pain, and pelvic computed tomography showed a pelvic mass attached to the uterus. As malignancy could not be ruled out, exploratory laparotomy with complete surgical staging was performed. The results of frozen section showed benign mesothelioma-like tumor. Unexpectedly, further histopathologic results of the lesion revealed a solitary fibrous tumor, an outcome that was subsequently confirmed by means of CD34 immunohistochemical stain. Conclusion: The behavior of solitary fibrous tumors arising from the uterus is difficult to evaluate; therefore, complete surgical excision featuring clear margins and comprehensive follow-up is recommended.